Cephalometric standards for 9 year-old Serbian children with neutroocclusion - Aleksić Ema Đ. (Acta Stomatologica Naissi, 2012)
Introduction. The populations show differences in relation to the various details of facial morphology. These differences are easily noticeable when comparing individuals with different ethnic background. Aim. To establish specific cephalometric standards between the sexes for the nine-year-old Serbian children. Methods. 36 boys and 42 girls (mean age 9±0.35) of Serbian nationality were selected based on the following criteria: Class I molar relationship, positive overbite and overjet less than 4mm, lack of crossbite, lack of oral and bucal failure, no previous orthodontic treatment, adequate amount of space in both dental arches, no visible asymmetry. Lateral cephalograms of each patient were analyzed twice. Descriptive statistics (mean, standard deviation, minimum and maximum) were calculated for all measured parameters. The results were compared to the published norms of the other Caucasian populations. Normative data were presented in the tables. Results. Intergender differences included anterior cranial base length (Sella-Nasion), anterior facial height (nasion-menton), corpus maxilla length, SNA angle, SNB angle, angle SN/MP. Conclusion. Nine-year-old Serbian boys have a larger anterior cranial base, larger corpus maxilla, and larger anterior facial height, while the maxilla and mandible protrusion are more pronounced in girls.